How Does Landscape Structure Affect Dung Beetle Assemblages in Amazon Cities? - Vanessa Pontes Mesquita; Glenda Vanessa dos Santos Bernardino; Paulo Estefano Dineli Bobrowiec; Renato Portela Salomão; Cintia Cornelius (Ecology and Evolution)
ABSTRACT The growth of cities is one of the main direct and indirect factors responsible for the loss of native vegetation cover. Urbanization directly affects the biological communities inhabiting forest remnants inserted in cities, compromising the maintenance of urban and natural ecosystems. By understanding the effects of landscape transformation due to urbanization, we can have insights regarding the distribution of land uses that allow a proper maintenance of the urban ecosystems. This work assessed the effects of landscape structure variables (forest cover, agricultural area, edge density, and number of forest patches) on dung beetle assemblages and functional groups (i.e., diet and resource removal strategy) sampled in 38 sites located along an urban–rural gradient of six cities belonging to the metropolitan area of Manaus in Central Amazonia. Losses of forest cover were the most determining factor, negatively affecting species richness, abundance, and body size. The increases in agriculture cover negatively affected dung beetle abundance, while edge density positively affected their abundance. The number of forest patches positively affected dung beetle abundances—except for dweller species—and negatively affected the body size of diet‐generalist species. These results demonstrate that changes in ecological diversity caused by urbanization are driven mostly by forest cover loss, although forest configuration is important for dung beetle abundance. This study contributes to the understanding of how changes in the amount and distribution of forest cover in tropical cities affect the taxonomic diversity of dung beetle assemblages.